Interdisciplinary Management Of Patients On Anticoagulant Therapy: Harmonizing Laboratory Monitoring And Nursing Care In Dental Practice (The Review of Diabetic Studies, 2024)
Background: The demographic shift towards an aging global population has precipitated a concurrent rise in the prevalence of cardiovascular diseases, necessitating the widespread prescription of anticoagulant therapies. While Vitamin K Antagonists (VKAs) such as warfarin have long served as the cornerstone of thromboembolic prevention, the advent of Direct Oral Anticoagulants (DOACs)—including dabigatran, rivaroxaban, apixaban, and edoxaban—has fundamentally altered the clinical landscape. These pharmacological agents, while effective in reducing stroke and systemic embolism, introduce significant complexity to dental management. The perioperative period in dental practice is characterized by a delicate equilibrium between the risk of surgical hemorrhage and the potentially catastrophic consequences of thromboembolism associated with anticoagulant interruption.Objectives: This comprehensive systematic review aims to synthesize current evidence regarding the interdisciplinary management of dental patients undergoing anticoagulant therapy. The primary objective is to harmonize the disparate elements of care—specifically laboratory monitoring (INR, renal function assessment) and nursing care interventions (anxiety reduction, preoperative education, triage)—to optimize patient safety and clinical outcomes. A secondary objective is to evaluate the efficacy of "continuation" versus "bridging" protocols and the specific role of local hemostatic measures in controlling post-extraction bleeding.Methods: A rigorous systematic review of the literature was conducted using major biomedical databases including PubMed, Scopus, and the Cochrane Library, covering publications through 2024. The search strategy targeted studies examining bleeding outcomes in dental procedures, pharmacological profiles of anticoagulants, and the impact of nursing interventions on dental anxiety and hemostasis. Inclusion criteria encompassed Randomized Controlled Trials (RCTs), cohort studies, and systematic reviews involving adult patients on VKAs or DOACs undergoing oral surgery. Data were extracted regarding bleeding severity, hemostatic techniques, anxiety scores, and interdisciplinary communication protocols.Results: Analysis of key clinical trials, including pivotal work by Karsli et al. and Al-Mubarak et al., indicates that for patients with an International Normalized Ratio (INR) within the therapeutic range (2.0–4.0), the continuation of warfarin therapy is superior to heparin bridging. Bridging therapy was associated with higher bleeding variability, increased cost, and no significant reduction in thromboembolic risk. For DOACs, evidence suggests that minor oral surgery can proceed safely without discontinuation, provided renal function (eGFR) is adequate and local hemostatic measures are employed. Crucially, the review identified that nursing interventions—specifically preoperative anxiety management through education and "tell-show-do" techniques—significantly reduce physiological stress responses (catecholamine release) that exacerbate bleeding.Conclusion: The clinical paradigm has decisively shifted from the routine interruption of anticoagulation to a strategy of continuation supported by local hemostasis. However, this shift demands a robust interdisciplinary safety net. Optimal management requires a collaborative model where nursing professionals play a pivotal role in bridging the gap between laboratory data and the dental operatory. By integrating rigorous preoperative assessment, anxiety control, and patient education, the interdisciplinary team can harmonize the competing demands of hemostasis and thrombosis prevention.